AN ANALYSIS OF IMAGERY IN CASA’S NOVEL *YUANFEN* - Salwa Khairunnisa; Sri Rahayu (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study aims to describe the forms of imagery found in the novel Yuanfen by Casa based on Pradopo’s theory of imagery. The research employed a qualitative approach using the content analysis method. The data consisted of words, phrases, sentences, and dialogues in the novel that contain imagery elements. Data were collected through reading and note-taking techniques, and then analyzed through the stages of identification, classification of imagery types, and interpretation of their meanings within the context of the story. The findings revealed that there are 90 instances of imagery in the novel Yuanfen, consisting of six types: visual imagery, auditory imagery, kinesthetic imagery, tactile imagery, gustatory imagery, and olfactory imagery. Kinesthetic imagery was found to be the most dominant type, followed by visual and auditory imagery. The use of imagery in the novel functions to clarify the depiction of events, settings, and the emotional conditions of the characters, enabling readers to imagine the situations in a more concrete and imaginative manner. Therefore, imagery plays an important role in building the readers’ aesthetic experience.